Central sensitization inventory in endometriosis - Orr, Natasha L.; Wahl, Kate J.; Lisonek, Michelle; Joannou, Angela; Noga, Heather; Albert, Arianne; Bedaiwy, Mohamed A.; Williams, Christina; Allaire, Catherine; Yong, Paul J. (Pain (Amsterdam), 2022)
A key clinical problem is identifying the patient with endometriosis whose pain is complicated by central nervous system sensitization, where conventional gynecologic treatment (eg, hormonal therapy or surgery) may not completely alleviate the pain. The Central Sensitization Inventory (CSI) is a questionnaire previously validated in the chronic pain population. The objective of this study was an exploratory proof-of-concept to identify a CSI cutoff in the endometriosis population to discriminate between individuals with significant central contributors (identified by central sensitivity syndromes [CSS]) to their pain compared to those without. We analyzed a prospective data registry at a tertiary referral center for endometriosis, and included subjects aged 18 to 50 years with endometriosis who were newly or re-referred to the center in 2018. The study sample consisted of 335 subjects with a mean age of 36.0 ± 7.0 years. An increasing number of CSS was significantly correlated with dysmenorrhea, deep dyspareunia, dyschezia, and chronic pelvic pain scores ( P < 0.001), and with the CSI score (0-100) ( r = 0.731, P < 0.001). Receiver operating characteristic analysis indicated that a CSI cutoff of 40 had a sensitivity of 78% (95% CI: 72.7%-84.6%) and a specificity of 80% (95% CI: 70.3%-84.5%) for identifying a patient with endometriosis with ≥3 CSS. In the group with CSI ≥ 40, 18% retrospectively self-reported pain nonresponsive to hormonal therapy and 40% self-reported daily pain, compared with 6% and 20% in the CSI < 40 group ( P = 0.003 and 0.002, respectively). In conclusion, a CSI ≥ 40 may be a practical tool to help identify patients with endometriosis with pain contributors related to central nervous system sensitization.